Insulin Modulates Cytokine Release, Collagen and Mucus Secretion in Lung Remodeling of Allergic Diabetic Mice - Ferreira, Sabrina S.; Nunes, Fernanda P. B.; Casagrande, Felipe B.; Martins, Joilson O. (Frontiers in Immunology, 2017)
Introduction: The role of insulin in lung remodeling in a model of asthma in healthy and diabetic mice was evaluated. Material and Methods: Diabetic male BALB/c mice [alloxan, 50 mg/kg, intravenous] and controls were sensitized by subcutaneous (s.c.) injection of ovalbumin (OA, 20 µg) in aluminum hydroxide [Al(OH)3, 2 mg] 10 days after the alloxan injection and received the same dose 12 days later. Six days after the last sensitization, animals were nebulized with OA solution for 7 days. The first set of diabetic and control mice received 2 IU and 1 IU, respectively, of s.c. neutral protamine Hagedorn (NPH) insulin and were analyzed 8 h later. The second set of diabetic and control mice received 2 IU and 1 IU, respectively, of insulin 12 h before the OA challenge and half doses of insulin 2 h before each the 7 OA challenges. Twenty-four hours after the last challenge, the following analyses were performed: a) quantification of the cells in the bronchoalveolar lavage fluid (BALF), the white cell count and blood glucose; b) morphological analysis of lung tissues by hematoxylin and eosin staining; c) quantification of collagen deposition in lung tissues and mucus by morphometric analysis of histological sections stained with Masson’s trichrome and periodic acid-Schiff (PAS), respectively; d) quantification of the cytokine concentrations (IL-4, IL-5 and IL-13) in the BALF supernatant. Results: Compared to controls, diabetic mice had significantly reduced inflammatory cells (81%) in the BALF, no eosinophils in the BALF and peripheral blood, and reduced collagen deposition and mucus in the lungs. BALF concentrations of IL-4 (48%) and IL-5 (31%) decreased, and IL-13 was absent. A single dose of insulin restored peripheral blood eosinophils and BALF mononuclear cells but not BALF eosinophils, collagen deposition and mucus levels. However, multiple doses of insulin restored both total cells and eosinophils in the BALF and peripheral blood, BALF cytokines, and collagen deposition and mucus secretion into the lungs. Conclusion: The results suggest that insulin modulates the production/release of cytokines, cell migration, deposition of collagen and mucus secretion in lung remodeling of a mouse model of asthma.